Effective calibration and validation of a nonlocal continuum damage model for laminated composites. (1st August 2017) - Zobeiry, N.; Forghani, A.; McGregor, C.; McClennan, S.; Vaziri, R.; Poursartip, A.
Abstract: A combined experimental and numerical approach is presented to calibrate the parameters of a previously developed nonlocal damage model used to simulate the inelastic response of laminated composites within a macroscopic modelling framework. In this approach, a limited number of physically-based damage parameters are obtained by conducting tests on notched specimens while employing the Digital Image Correlation (DIC) technique. These parameters are then used to calibrate a non-local sub-laminate based damage mechanics model, CODAM2. Compared to available ply-based approaches; the sub-laminate damage model reduces the computational time significantly while capturing the overall damage behaviour of the laminate. The damage model is implemented as a built-in material model in the commercial finite element code, LS-DYNA (MAT_219) and also in the open-source object oriented finite element code, OOFEM. To validate this approach, experiments were conducted on notched tensile specimens with varying notch-tip radii that result in a range of behaviour from stable to unstable damage growth as this radius increases. The calibrated damage model was used to predict this transition.